CONTEMPORARY ASPECTS OF RUSSIAN MEDIA (THE INFLUENCE OF COMMUNISM INHERITANCE) - Irina Kulenovic (European Scientific Journal, ESJ, 2014)
Russian media came through a long path of development to todays adjective of free and independent, at least on declarative level. A special accent is on the fact that Russian journalist no matter the field of law, fund the way to publish investigative facts and to stand on the side of undesirable oponent opinion. Those kind of jornalists put a side any ideological or political obstacles which appear in their professional work. This work is dedicated mostly to them. Our research started from journalism and all of its characteristics during the Soviet Union period, because that part of Russian history affected the most on today's state of media in Russia. Years which followed the breakdown of Soviet Union are our later fields of concentration, especially the incoming democratization and liberalization of the system and journalism itself. We made an overview of normatives and legal framework which today's media in Russia are functioning on and also, we've looked back on the way and the system on which young journalists in Russia educate themselves today. All of these are very important factors and issues needed to be explained in order to enlighten all contemporary aspects of the Russian media today. There are always the causes and the results. Basically looked, the main social studies on Russia's society are offernig us a conclusion that it is highly centralized and that represents the main issue and obstacle in the process of full democratization of that former communist society. We've questioned ourselves...why is the Russia on today's 148 place by the media freedom in the world?